2003
DOI: 10.1128/cmr.16.2.273-307.2003
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoebaspp. as Agents of Disease in Humans

Abstract: Acanthamoeba spp. are free-living amebae that inhabit a variety of air, soil, and water environments. However, these amebae can also act as opportunistic as well as nonopportunistic pathogens. They are the causative agents of granulomatous amebic encephalitis and amebic keratitis and have been associated with cutaneous lesions and sinusitis. Immuno compromised individuals, including AIDS patients, are particularly susceptible to infections with Acanthamoeba. The immune defense mechanisms that operate against A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
1,039
0
38

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,120 publications
(1,084 citation statements)
references
References 416 publications
(506 reference statements)
7
1,039
0
38
Order By: Relevance
“…Comparison of the incidence and EAE severity induced by PLP 139151 with that of ACA 83-95 revealed that ACA 83-95 induced clinical and/or histological EAE in only 72.7% of animals and the disease severity was mild ( Figure 2 and Table 2 (Marciano-Cabral and Cabral, 2003). In our studies with ACA 83-95, although MNC were present, the dominance of plasma cells and giant cells was absent.…”
Section: Aca 83-95 Induces T Cell Responses That Cross-react With Plpmentioning
confidence: 47%
See 1 more Smart Citation
“…Comparison of the incidence and EAE severity induced by PLP 139151 with that of ACA 83-95 revealed that ACA 83-95 induced clinical and/or histological EAE in only 72.7% of animals and the disease severity was mild ( Figure 2 and Table 2 (Marciano-Cabral and Cabral, 2003). In our studies with ACA 83-95, although MNC were present, the dominance of plasma cells and giant cells was absent.…”
Section: Aca 83-95 Induces T Cell Responses That Cross-react With Plpmentioning
confidence: 47%
“…ACA is a free-living organism present throughout the world habituating in water, soil, and dust, and it causes AGE, amoebic keratitis and cutaneous amoebiasis in infected humans (Claerhout and Kestelyn, 1999;Marciano-Cabral and Cabral, 2003). AGE is a chronic progressive disease of the CNS commonly seen in chronically ill, debilitated, or immunocompromised individuals such as AIDS patients (Marciano-Cabral and Cabral, 2003). The amoebae activate phosphatidylinositol 3-kinase to induce apoptosis of brain microvascular endothelial cells and successfully traverse the blood-brain barrier to induce AGE (Sissons et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They have also been isolated from hydrotherapy baths, dental irrigation equipments, humidifiers, cooling systems, ventilators, and intensive care units (Marciano-Cabral et al, 2003). Acanthamoeba species can exist as either dormant cysts or as the active trophozoites (Khan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…21,22,25 Diagnostic techniques that do not rely on visualization of trophozoites, such as polymerase chain reaction, have been developed. 7,[26][27][28] As molecular techniques are being applied more frequently for diagnosis of a variety of infectious agents, falsepositive reactions will occur. Thus, molecular results have to be correlated with epidemiologic, clinical, and pathologic features.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Other diagnostic techniques, including microscopy of wet mounts, histopathology, electron microscopy, immunocytochemistry (such as immunofluorescence, flow cytometry), and culture, rely on identification of trophozoites and cysts in cerebrospinal fluid or brain tissue specimens. 1,7,8 Previous histopathologic reports describe single cases or small series of patients infected by one amebic genus. [9][10][11][12][13][14][15][16][17][18][19][20] Side-by-side histopathologic comparison of cases caused by different ameba is not available.…”
mentioning
confidence: 99%